Genetic markers in breast cancer – how far fave we come from BRCA1? - Avery-Kiejda, Kelly A.; Wong, Michelle W.; Scott, Rodney J. (UKM Medical Molecular biology Institute, UMBI, 2011)
Breast cancer is the most common malignancy that develops in women worldwide, its incidence continues to rise and it is responsible for the highest death rates. Breast cancer can be classified as sporadic or familial – the strongest risk factor today is a family history. Germline mutations in high-penetrance breast cancer susceptibility genes BRCA1 and BRCA2 have been strongly implicated in the genetic predisposition of approximately 20% of familial breast cancers. Although BRCA1 and BRCA2 do not account for all familial breast cancers, there are currently no other genes that have been identified which segregate with familial breast cancer as strongly. Despite large-scale attempts to identify genetic risk factors associated with breast cancer, the variants identified through genome-wide association studies (GWAS), only confer a modest increase in risk of breast cancer and at present lack clinical utility. This review will discuss the known genetic risk factors for developing breast cancer and how far the field has progressed since the identification of BRCA1.